Re-Live History: An immersive virtual reality learning experience of prehistoric intangible cultural heritage - Barbara, Jonathan (Frontiers in Education, 2022)
The use of immersive virtual reality for learning is a growing opportunity that has so far suffered from limited application in the classroom, particularly with younger students. Due to more concern being shown towards usability rather educational goals, mixed feelings exist about the technology’s ability to teach. Meanwhile, historical games usually have fun as the main or sole objective, which may cause problems by diminishing the value of the depicted cultural heritage and supersede the intended learning outcomes of the experience. This research aims to contribute towards this gap by working closely with teachers in developing an immersive virtual reality learning experience to teach prehistoric intangible cultural heritage to Level 7 history students. The research question of this study is how to go about designing an immersive learning experience for secondary school teachers to teach students about prehistoric cultural heritage on which very little documented evidence is available. To this end, the ReLiveHistory project was built upon a virtual reality navigation experience of a Maltese Neolithic hypogeum, adding a representation of intangible cultural heritage in the form of human behavior. A content requirement study from heritage experts’ perspective was carried out, followed by a similar study from the history teachers’ perspective. These provided which learning outcomes can be potentially addressed by the immersive learning experience, what form of intangible cultural heritage can be represented, and what success criteria were to be used for its evaluation. A prototype of the experience was then developed and reviewed by the heritage experts and subsequently developed into the experience evaluated by teachers and heads of department. Evaluation was carried out in terms of authenticity relative to the historic site, ease of navigation, impact in terms of achievable learning outcomes, and utility in the classroom. This ensured that educational objectives were given priority and should help teachers embrace and adopt the technology in the classroom. Future work should pilot the use of the IVR in the classroom and provide further empirical evidence to its ability to help students achieve the learning outcomes expected by the syllabus.